Hybrid Archival Practices in the Bureaucracy of Population Administration Services: A Qualitative Study of the Dispendukcapil of Malang City - Atmojo, Prisilia Joyceline; Hermanto, Febrika Yogie (Universitas Negeri Surabaya, 2025)
This study examines hybrid archival management practices within the population administration service bureaucracy at the Dinas Kependudukan dan Pencatatan Sipil of Malang City as a phenomenon reflecting the tension between the public service digitalization agenda and the need for conventional administrative control. Although population information systems have been implemented to support electronic-based services, physical and digital archiving practices continue to be carried out simultaneously through processes of printing, manual verification, physical recording, rescanning, and digital storage. This study aims to elucidate how hybrid archival practices are executed in the day-to-day operations of the population bureaucracy, the organizational rationality underlying their persistence, and their implications for administrative burden, accountability, and the sustainability of records governance. The research employs a qualitative approach with a case study design. Data were collected through semi-structured in-depth interviews with ten purposively selected informants, direct observation of service and archiving processes, and documentation studies of procedures and archival records. The results indicate five main findings: hybrid archiving has been institutionalized as an administrative work routine; dual record-keeping is maintained as a mechanism for organizational security and legitimacy; hybrid archival practices generate significant administrative burden and work pressure; employees develop informal work practices as adaptation strategies; and employee perceptions of hybrid archiving are ambivalent regarding digital efficiency versus physical accountability. This study implies the need for more realistic and contextual archival policies, strengthening of cross-unit records governance, and enhancement of human resource capacity and digital record legitimacy to ensure that public archival transformation proceeds effectively and sustainably.